2020
DOI: 10.1155/2020/9131850
|View full text |Cite
|
Sign up to set email alerts
|

Quality Indicators of Pharmaceutical Care for Integrative Healthcare: A Scoping Review of Indicators Developed Using the Delphi Technique

Abstract: Background. Recently, measuring and benchmarking provision of healthcare services has drawn a considerable attention. This scoping review was conducted to identify, describe, and summarize studies in which the Delphi technique was used to develop quality indicators of pharmaceutical care. The study also aimed to identify activities and services that could be used to capture the impact of pharmacist in integrative medicine. Methods. Databases were searched from inception to February 2020 using key terms that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 77 publications
0
32
0
Order By: Relevance
“…Another core list of consensual key performance indicators that can serve in capturing performance of clinical pharmacists while caring for patients in hospitalized patient settings was developed [22]. A recent scoping review identified 42 different pharmaceutical activities and services that can be used as to measure quality of pharmaceutical care for integrative healthcare [24]. e activities and services that were developed using the Delphi technique included taking medication history, medication reconciliations, resolving therapy-related problems, provision of collaborative care, formulating therapeutic plans, optimal performance, and continuing education.…”
Section: Introductionmentioning
confidence: 99%
“…Another core list of consensual key performance indicators that can serve in capturing performance of clinical pharmacists while caring for patients in hospitalized patient settings was developed [22]. A recent scoping review identified 42 different pharmaceutical activities and services that can be used as to measure quality of pharmaceutical care for integrative healthcare [24]. e activities and services that were developed using the Delphi technique included taking medication history, medication reconciliations, resolving therapy-related problems, provision of collaborative care, formulating therapeutic plans, optimal performance, and continuing education.…”
Section: Introductionmentioning
confidence: 99%
“…This study was part of a larger study that was conducted to develop a consensus-based core inventory of KPIs to be used in capturing the impact of pharmaceutical care in healthcare facilities that employ integrative medicine paradigm [ 33 , 34 ]. The present study is being reported in compliance with the Conducting and REporting of Delphi Studies (CREDES) guidelines [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Activities performed and services provided by pharmacists while caring for patients admitted to or visiting healthcare facilities that employ integrative medicine that potentially can be used as KPIs were collected from the literature into an initial inventory [ 33 ]. The list of activities and services collected from the literature was supplemented by additional activities and services that were provided by 9 CAM practitioners, 8 pharmacists, 2 physicians, 2 nurses, and 1 risk/quality assurance manager who were interviewed using in-depth semistructured qualitative interviews [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it is considered to be an effective method for gaining judgments on complex matters where precise information is unavailable [ 87 ]. In addition, the DELPHI method has been widely used to determine consensus in a number of important need areas, especially in the healthcare field [ 88 , 89 , 90 ].…”
Section: Application Of the Proposed Framework: Case Of The Moroccmentioning
confidence: 99%